Physical properties, chemical composition, and nutritional evaluation of common salad dressings - Yin, Mingyu; Chen, Min; Yanagisawa, Takuya; Matsuoka, Ryosuke; Xi, Yinci; Tao, Ningping; Wang, Xichang (Frontiers in Nutrition, 2022)
Salad dressings (SDs), a subcategory of flavored sauces with more than 20% fat content and less than 30% moisture content, is favored by consumers due to its delicacy. The physical properties, chemical composition and nutritional evaluation of common SDs on the Chinese market needs to be systematically investigated.This study compared the quality (physical properties, proximate composition, amino acids, fatty acids, and minerals) of six commercially available sweet SDs (SD1, SD2, SD3, SD4, SD5, and SD6) from the Chinese market.The results indicated that the water activity of six SDs was less than 0.60 (0.35–0.41), the moisture content was less than 65% (24.0%–60.0%), and the crude fat content was between 23.25% and 64.15%. The essential amino acid index (EAAI) of SD3, SD1, SD2, and SD4 was greater than the FAO/WHO standard (EAAI = 75). Numerous fatty acids were detected, mainly linoleic and oleic acids. In addition, SDs were rich in minerals such as Mg, Ca, and Fe and the atherogenic index and thrombogenic index were 0.03–0.09 and 0.77–0.91, respectively. In summary, this work helps to provide key nutritional information on the composition of common SDs. The availability of this data may help purchasers with different nutritional needs to make informed choices about the use of SD and encourage more moderate consumption of pre-packaged sauces.